Pengaruh Kemudahan, Keamanan, dan Inovasi Teknologi terhadap Kepuasan Pengguna dengan Preferensi Platform Pembayaran Digital sebagai Variabel Moderasi - Nur Fatimah, Ambar Lena; Widayati, Ani (Lembaga Teewan Journal Solutions, 2026)
Digital transformation in the financial sector has accelerated the adoption of digital payment platforms such as e-wallets in Indonesia. This study aims to examine the effect of ease of use, transaction security, and technological innovation on user satisfaction, with digital payment platform preference as a moderating variable. The study employs a quantitative approach using a survey method with 200 respondents who are active users of digital payment services in Yogyakarta. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) with SmartPLS 4. The results show that ease of use has a positive and significant effect on user satisfaction, indicating that simpler and more user-friendly systems increase satisfaction levels. Transaction security also has a positive and significant effect, highlighting the importance of data protection and transaction safety in shaping user trust and satisfaction. Furthermore, technological innovation significantly influences user satisfaction, suggesting that feature development and system integration enhance user experience. However, digital payment platform preference does not moderate the relationship between ease of use, security, and technological innovation on user satisfaction. Overall, the model explains 74.6% of the variance in user satisfaction, indicating strong predictive relevance. These findings emphasize that usability, security, and innovation are key determinants of digital payment satisfaction in the context of financial technology adoption.